2016
DOI: 10.1111/ejn.13395
|View full text |Cite
|
Sign up to set email alerts
|

Acute stress alters individual risk taking in a time‐dependent manner and leads to anti‐social risk

Abstract: Decision-making processes can be modulated by stress, and the time elapsed from stress induction seems to be a crucial factor in determining the direction of the effects. Although current approaches consider the first post-stress hour a uniform period, the dynamic pattern of activation of the physiological stress systems (i.e., the sympathetic nervous system and hypothalamic-pituitary-adrenal axis) suggests that its neurobehavioural impact might be heterogeneous. Here, we evaluate economic risk preferences on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 53 publications
0
53
3
Order By: Relevance
“…Specifically, this sample size was attained by predicting a small-to-medium effect size based on previous research examining effects of stress on similar constructs (e.g., Bendahan et al, 2016, Starcke & Brand, 2016, using an alpha level of .05, power of .80, and six predictors.…”
Section: Participantsmentioning
confidence: 99%
“…Specifically, this sample size was attained by predicting a small-to-medium effect size based on previous research examining effects of stress on similar constructs (e.g., Bendahan et al, 2016, Starcke & Brand, 2016, using an alpha level of .05, power of .80, and six predictors.…”
Section: Participantsmentioning
confidence: 99%
“…Multiple studies have reported risk-taking increases when decisions are framed as potential financial gains [64–66], though longer stress-to-task latencies have recently been shown to be a factor with respect to decisions under risk [i.e., greater risk taking immediately after stress but reduced risk-taking 45 minutes later; 67] Other studies separating decisions under risk by domain (gain/loss trials) are inconsistent. For instance, acute systemic stress applied in that context has led to an exaggerated reflection effect (i.e., decreased risk-taking for gains but increases for losses) interpreted as a stress-related shift towards habit-based DM [68].…”
Section: Stress and Risk-takingmentioning
confidence: 99%
“…Bendahan et al. () examine risk preference at three time points—immediately, 20 minutes, and 45 minutes after the onset of TSST‐induced stress—and observe a time‐dependent change from lower to greater risk aversion. Wälde () provides a theoretical analysis on stress and coping.…”
Section: Introductionmentioning
confidence: 99%
“…Using TSST to induce stress, Cahlíková and Cingl (2016) show that exogenously induced psychosocial stress significantly increase risk aversion, especially for men. Bendahan et al (2017) examine risk preference at three time points-immediately, 20 minutes, and 45 minutes after the onset of TSST-induced stress-and observe a time-dependent change from lower to greater risk aversion. Wälde (2015) provides a theoretical analysis on stress and coping.…”
Section: Introductionmentioning
confidence: 99%